Organizational Change and Culture in Post-Merger Transformation:Talent Management as a Strategic Integration Mediator - Ciptaningtias, Mardiana; Suryani, Tatik (Universitas Muhammadiyah Pontianak, 2025)
An organization is only as good as its people. The success of an organization is highly dependent on the management of its human resources, especially in the context of post-merger transformation that demands the integration of structure, culture, and work systems. This study aims to examine the role of talent management as a strategic mediator in the relationship between organizational change and organizational culture on employee performance. The study was conducted at PT Angkasa Pura Indonesia Juanda International Airport Branch Office using a quantitative approach with SEM-PLS analysis techniques on 202 respondents. The results of the study indicate that organizational culture has a positive effect on talent management and employee performance, and talent management significantly mediates the relationship. However, organizational change does not have a significant effect on talent management or employee performance indirectly. This finding suggests that talent management that is aligned with organizational culture has a greater impact on performance than structural change alone. This finding provides a theoretical contribution to the literature on strategic human resource management in the post-merger context in driving performance. This study also provides practical implications for organizations in designing talent-based integration strategies to achieve sustainable competitive advantage